Contribution of ultrasonic to microstructure and mechanical properties of tilt probe penetrating friction stir welded joint. (20th September 2021) - Hu, Yanying; Liu, Huijie; Li, Dongrui
Graphical abstract: Highlights: A novel welding technique, namely ultrasonic enhanced tilt probe penetrating friction stir welding (U-PFSW), is proposed. Ultrasonic facilitates atomic diffusion and aids in relieving the coherency strain to enhance θ՛ precipitation strengthening. Dynamic recrystallization in U-PFSW is significantly accelerated, contributing to a complete elimination of "S" line. Joint strength and ductility are both improved by the U-PFSW. Abstract: Tilt probe penetrating friction stir welding (PFSW) was an innovative technology proposed in recent years to avoid the formation of kissing bond in the root of joint. However, with the heat input decreasing, "S" line or zigzag line was easily introduced in the PFSW joint. In this study, ultrasonic enhanced tilt probe penetrating friction stir welding (U-PFSW) was developed to solve this problem and achieve improved joint mechanical properties. The experimental results confirmed that U-PFSW was a potent technology to completely clear the original butt surface, providing a crucial prerequisite for the achievement of high-strength joint. The application of ultrasonic improves the joint tensile strength and fracture elongation from 336 MPa and 4.3% to 359 MPa and 6.8 %, respectively. Furthermore, the strength of stir zone was also increased from 391 MPa in PFSW to 420 MPa in U-PFSW. Analyses of texture and precipitate indicated that the dynamic recrystallization (DRX) and precipitation strengthening were both enhanced by the ultrasonic. Ultrasonic-enhanced DRX enabled a complete elimination of the "S" line; the enhanced precipitation strengthening by vacancy-induced mechanism in U-PFSW was the intrinsic reason for the significantly improved mechanical properties.